PENGARUH MACHIAVELLIAN, INDEPENDENCE, DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT DENGAN DYSFUNCTIONAL BEHAVIOR SEBAGAI VARIABEL MODERASI - Aldi Rivaldi (2021)
The quality of the audit produced by an auditor in carrying out his work greatly affects the level of trust held by the public as users of financial statements on the accounting profession. Indirectly, this illustrates that the responsibility of the auditor is not only focused on the community but also on the existence of the profession. The purpose of this study is to examine and empirically prove the effect of machiavellian characteristic, independence, and time budget pressure on audit quality moderated by dysfunctional behavior. The population of this research is the auditors who are in the AKN V and VI units of BPK RI. The sample of this research consisted of 52 respondents and used purposive sampling method. The data analysis using Structural Equation Modelling (SEM) with SmartPLS software version 3.0. The result of this study conclude that independence and time budget pressure has a significan effect on the audit quality. Machiavellian characteristic doesn't have significantly effect audit quality. Dysfunctional behavior doesn't moderate the effect of machiavellian characteristic, independence, and time budget pressure with audit quality. Keywords: Audit Quality, Machiavellian Characteristic, Independence, Time Budget Pressure, and Time Budget Pressure.